Posterior interosseous nerve lesion due to lipoma - Rojc, Bojan (Radiology and oncology (Ljubljana), 2024)
Background. Posterior interosseous nerve lesion is a rare mononeuropathy of the upper limb. Atraumatic posterior interosseous nerve lesions are commonly caused by lipomas of the forearm, manifesting as slow-progressing wrist and finger drop. Patients and methods. In this review and case report study, we present a systematic review of the literature for patients presenting with posterior interosseous palsy due to lipomas and a rare case of patient with acute posterior interosseous nerve lesion caused by a lipoma. Our primary interest was in the timing of clinical presentation. For the review process, we followed the Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. Results. After reviewing the literature, we identified thirty patients with posterior interosseous nerve lesions caused by lipomas. In 28 patients, the symptoms presented progressively, ranging from 1 month to a maximum of 240 months. We found only one case of a patient with acute presentation and another patient with acute worsening of chronic weakness due to trauma. Conclusions. Atraumatic posterior interosseous nerve lesions are frequently secondary to forearm lipomas. In the majority of cases, the symptoms will develope progressively. However, in this study, we also report a rare case of a patient presenting with acute posterior interosseous nerve lesion due to a lipoma.
Keywords: lipom; postakutna kompresija; posteriorni medkostni živec; redka mononevropatija zgornjega uda